Adult development and aging - Cavanaugh, John C.; Blanchard-Fields, Fredda (Australia : Cengage Learning, 2015)
"Written within a bio-psychosocial framework, ... [that] covers the specific ages/stages of adult development and aging. In its unparalleled coverage of current research and theory, the authors draw clear connections between research and application. The book's focus on "positive aging" and the gains and losses people experience across adulthood distinguish it."--Provided by publisher.
Current Controversies: What to Do About Social Security and Medicare -- Adult Development in Action -- 14.2.Health Issues and Quality of Life -- Health Promotion And Quality Of Life -- A Framework For Maintaining And Enhancing Competence -- Health Promotion And Disease Prevention -- Lifestyle Factors -- Adult Development in Action -- 14.3.Successful Aging -- Discovering Development: What Is Successful Aging? -- Approaches To Successful Aging -- Critiques Of The Successful Aging Framework -- Epilogue -- Summary -- Review Questions -- Integrating Concepts In Development -- Key Terms -- Resources.
Includes bibliographical references (pages R1-R32) and indexes.
Keywords: Adulthood -- Psychological aspects -- Textbooks; Aging -- Psychological aspects -- Textbooks; Adulthood -- Physiological aspects -- Textbooks; Aging -- Physiological aspects -- Textbooks; Aging -- Social aspects -- Textbooks; Aging -- psychology; Adult; Adaptation, Psychological; Social Adjustment; Aging -- Physiological aspects; Adulthood -- Physiological aspects; Adulthood -- Psychological aspects; Aging -- Psychological aspects; Aging -- Social aspects; Textbooks